Embryotoxicity and teratogenicity studies on artemether in mice, rats and rabbits - CHEN Li-jian; WANG Mei-ying; SUN Wei-kang; LIU Ming-zhang (Acta Pharmacologica Sinica, 2016)
Artemther (methyl-dihydroartemisinine) is a new antimalarial agent derived from qinghaisu (artemisinine). When the mice were given im 0.7 or 5.4 mg/kg/d on d 6-15 of gestation, no adverse effects on the fetuses were seen. At 10.7 and 21.4mg/kg/d, 30% and 100% of the surviving fetuses remained normal. Their second generations appeared to be normal. In rats with a dose of 21.4mg/kg/d on d 9-11, all embryos were resorbed. The embyyotoxicity of artemether in rats and rabbits was similar to that in mice. No teratogenic effects were observed in mice, rats and rabbits. Parallel expreriments in rats with aspirin 250 mg/kg/d showed that 66% of the embryos were resorbed and 36% of the remaining fetuses exhibited exhibited external malformations (P＜0.01).